Rajaresurssien puute hidastaa teollisen internetin alustaekosysteemien syntyä; The Lack of Boundaries Resources Hinders the Growth of Industrial Internet - Klaus Castren; Aleksi Kortelainen; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2016)
– We analyze 51 medium-sized manufacturing industry companies identified by Ali-Yrkkö and Rouvinen in their earlier research in 2015. Currently, out of these 51 companies with a staff of 250–499 employees in 2013, none are using digital platforms for business network management. It is typical for digital platforms that different actors can create, provide and maintain complementary products and services to the various distribution channels and markets, within the framework of mutually agreed business and contract rules, technical bourdary resources and a predefined user experience. Only seven companies (14%) offer digitally featured products and services. Digital product and service features are charted by using 26 different Finnish and English search terms, such as 'internet of things', 'sensor', 'cloud service' and 'preventive maintenance'. Finally we consider four strategic questions for open boundary resources.
Keywords: L6; L8; L86; L89; 330; Digital platforms; Boundary resources; Digital offering; Kemppi; Internetportal; Unternehmensnetzwerk; Virtuelle Organisation; Finnland